Link2U: un social network aumentato su dispositivi mobili - Sebillo, Monica; De Chiara, Davide; Romano, Marco; Vitiello, Giuliana (GEOmedia, 2012)
Negli ultimi anni il connubio mobile entertainment e social network ha attirato un notevole interesse da parte dispecifici settori che, nonostante le criticità del momento, hanno deciso di investire nella realizzazione di ambienti esoluzioni di intrattenimento/divertimento, un fattore chiave alla base del miglioramento della tecnologia. Link2U: augmenting social networks on mobile devices Nowadays, modern mobile devices have become real person-al computers that increase the ability of building/extending existing applications by combining several technologies such as camera, GPS, 3D graphics and permanent Internet connec-tion. The resulting integration of such technologies allows to run complex applications, such as augmented reality and Social Networks. The goal of our current research is to support mobile users' daily activities, by developing advanced solutions which take into account principles of human-computer interac-tion and usability. In this paper we propose to exploit the potential of the aug-mented reality and the ability to communicate of social net-works to create a mobile social network, where each commu-nity user may exploit advanced location based services, such as navigation through a two dimensional map, exploration of an area through a camera mode, and identification of points of interest embedded in an augmented reality environment.